The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1590/s0034-71082000000200004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the infestation by Lernaea cyprinacea Linnaeus, 1758 (Copepoda, Lernaeidae) on the leucocytes of Schizodon intermedius Garavello & Britski, 1990 (Osteichthyes, Anostomidae)

Abstract: Differential white blood cell counts from Schizodon intermedius infested by Lernaea cyprinacea were carried out and compared using the Wilcoxon matched pairs test. The observations were performed in fish infested by 16-77 adult Lernaea, fish with parasitic lesions but without attached crustaceans, and non parasitized fish (control group). The specimens of Schizodon intermedius were obtained from the University of Londrina fish farming facilities. The following leucocytes were observed: lymphocytes, neutrophils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 10 publications
4
11
0
2
Order By: Relevance
“…In both the infested and basal (uninfested) groups, we found that lymphocytes are the most abundant leukocytes in the peripheral blood; however, eosinophils were scarce in the uninfested fishes but abundant in the infested ones, which correlates with other studies in fishes (ALVAREZ-PELLITERO, 2008;EZE EVELYN et al, 2012;PIERRARD et al, 2012;RUANE et al, 2000;SILVA-SOUZA et al, 2000). Neutrophils decrease steadily during the 4 weeks of infestation, which is consistent with a study by Tavares-Dias et al (2008).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In both the infested and basal (uninfested) groups, we found that lymphocytes are the most abundant leukocytes in the peripheral blood; however, eosinophils were scarce in the uninfested fishes but abundant in the infested ones, which correlates with other studies in fishes (ALVAREZ-PELLITERO, 2008;EZE EVELYN et al, 2012;PIERRARD et al, 2012;RUANE et al, 2000;SILVA-SOUZA et al, 2000). Neutrophils decrease steadily during the 4 weeks of infestation, which is consistent with a study by Tavares-Dias et al (2008).…”
Section: Discussionsupporting
confidence: 92%
“…Sea louse cause a local inflammatory response and blood loss at the site of attachment but do not appear to suppress host defense mechanisms during the early stages of infestation (TAVARES-DIAS et al, 2007;WAGNER et al, 2008). Parasitic infestations can influence blood parameters, such as anemia and white cells count unbalances in other host fishes (HORTON;OKAMURA, 2003;MARTINS et al, 2004;SILVA-SOUZA et al, 2000;TAVARES-DIAS et al, 1999, 2002WAGNER et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Parasites affect fish health, growth and survival (Barson and Marshall, 2003). Lernaea cyprinacea Linnaeus, 1758 (Crustacea: Copepoda), commonly known as "anchor worm", is an important crustacean parasite of freshwater fish that has a wide geographic range (Silva-Souza et al, 2000;Nagasawa et al, 2007;Hoffman, 1999). Lernaea species have nine stages in the life cycle, including three free-living naupliar stages, five copepodid stages and one adult stage.…”
Section: Introductionmentioning
confidence: 99%
“…Alterações no quadro hematológico de peixes expostos a metais pesados foram observadas em Hoplias malabaricus (OLIVEIRA-RIBEIRO et al, 2006), em Acipenser baeri (MIKRYAKOV e LAPIROVA, 1996), em Oreochromis niloticus (NUSSEY et al, 1995;ISHIKAWA, 2003), em Oreochromis aureus (ALLEN, 1994), em peixes parasitados (SILVA-SOUZA et al, 2000, MARTINS et al, 2004, RANZANI-PAIVA et al, 2005AZEVEDO et al, 2006a), o efeito do estresse por restrição alimentar em Hoplias malabaricus (RIOS et al, 2005), de toxinas (GORDON et al, 2005;MOLINA et al, 2005) e contaminação bacteriana (RANZANI-PAIVA et al, 2004;SILVEIRA-COFFIGNY et al, 2004;MISRA et al, 2006a).…”
Section: Introductionunclassified